How to rock braces and glasses : a novel - Haston, Meg (New York : Little, Brown and Company, 2011)
When popular middle schooler Kacey Simon gets glasses and braces and is rejected by her crowd, she befriends a boy who is in a punk rock band and discovers some things about friendship, relationships, and herself.
Primary
Keywords: Middle schools -- Fiction; Popularity -- Fiction; Rock groups -- Fiction; Schools -- Fiction; Bands (Music) -- Fiction; Interpersonal relations -- Fiction